2020
DOI: 10.3390/ijms21176259
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Folding and Dimerization Mechanisms of the N-Terminal Domain from Human TDP-43

Abstract: TAR DNA-binding protein 43 (TDP-43) is a 414-residue long nuclear protein whose deposition into intraneuronal insoluble inclusions has been associated with the onset of amyotrophic lateral sclerosis (ALS) and other diseases. This protein is physiologically a homodimer, and dimerization occurs through the N-terminal domain (NTD), with a mechanism on which a full consensus has not yet been reached. Furthermore, it has been proposed that this domain is able to affect the formation of higher molecular weight assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
5
16
0
Order By: Relevance
“…Accordingly, following S-nitrosylation of TDP-43, an intramolecular disulfide bond between Cys173 and Cys175 results in a conformational change facilitating aggregation (29,31). Interestingly, an intermolecular disulfide linkage was recently reported to occur at Cys244 between two TDP-43 protein molecules (30), producing TDP-43 dimers and oligomers (69,70). In the present study, our molecular dynamics simulations suggested that the intramolecular disulfide bridge that we observed between Cys173 and Cys175 would trigger conformational alterations leading to increased solvent exposure at Cys244, potentially facilitating intermolecular disulfide linkage at that residue.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, following S-nitrosylation of TDP-43, an intramolecular disulfide bond between Cys173 and Cys175 results in a conformational change facilitating aggregation (29,31). Interestingly, an intermolecular disulfide linkage was recently reported to occur at Cys244 between two TDP-43 protein molecules (30), producing TDP-43 dimers and oligomers (69,70). In the present study, our molecular dynamics simulations suggested that the intramolecular disulfide bridge that we observed between Cys173 and Cys175 would trigger conformational alterations leading to increased solvent exposure at Cys244, potentially facilitating intermolecular disulfide linkage at that residue.…”
Section: Discussionmentioning
confidence: 99%
“…The non-native unfolded intermediate states might facilitate protein oligomerization and aggregation. Very recently, Vivoli-Vega et al ( 2020 ) biophysically characterized the folding/dimerization of NTD and identified a head-to-tail arrangement during the dimerization of NTD. The authors also found that the folding of NTD proceeds through the formation of a collapsed state and an intermediate state.…”
Section: Discussionmentioning
confidence: 99%
“…Through all-atom MD simulation, we have studied the stability and dynamics of the NTD mutations, L27A, L28A, and V31R, and provide insights into the mechanisms of the destabilization of NTD variants (Kumar et al, 2019 ). A recent study also demonstrated the presence of different partially folded states during the folding pathways of NTD (Vivoli-Vega et al, 2020 ). Therefore, the folding dynamics and confirmational stability studies of NTD are essential to underpinning the role of folding intermediates behind the dichotomy of TDP-43.…”
Section: Introductionmentioning
confidence: 86%
“…For example, another member of the hnRNP family, hnRNP C, can multimerize which improves its binding to RNA by a cooperative RRM dimer binding model (CienikovĂĄ et al, 2015). TDP-43 can also dimerize via its N-terminal region (RBD) (Vivoli-Vega et al, 2020). Interestingly, TDP-43 dimers are enriched in the cytoplasm and found in physiological conditions as well as in ALS patient brains (Shiina et al, 2010).…”
Section: Discussionmentioning
confidence: 99%